Predictive value of CRP and albumin ratio in neonatal sepsis - Athmananda, Chandana; K. B., Mahendrappa; Unki, Praveen; Kumar, Hemanth; Kerudi, Madhu P.; Babu, Keerthana T. (International Journal of Contemporary Pediatrics, 2023)
Background: The role of hypoalbuminemia and raised C-reactive protein (CRP) levels in predicting critical prognosis has been described extensively in adult literature. However, there are limited studies in pediatrics, particularly neonates. The study was conducted to assess the predictive value of the CRP vs Serum albumin in earlier identification and as a prognostic indicator of neonatal sepsis. Methods: In this research, from July 2021 to February 2022 a total of 150 studies were enrolled at Adichunchanagiri Institue of medical sciences. Complete clinical and laboratory data were collected. To identify the potential independent risk factor for neonatal sepsis, multivariate logistic regression analysis was performed. Receiver operating characteristic curve analysis was used to evaluate the prediction accuracy of CAR in identifying neonatal sepsis. Results: A total of 150 neonates were included in the study out of which 78 neonates were preterm, 32 neonates were late preterm and 40 neonates were term neonates. CAR levels were higher in neonates with sepsis and showed a gradual increase among the control group, mild sepsis group, and severe sepsis group. The prevalence of neonates with overall sepsis, mild sepsis, and severe sepsis increased significantly from CAR tertile 1 to tertile 3. Multiple logistic regression analysis showed that CAR was an independent risk factor for the presence of sepsis (OR = 11.123, 95% CI 6.74–14.5, p<0.001) and severe sepsis (OR=1.568, 95% CI 1.3-2.4, p<0.001). ROC curve analysis showed that CAR had a well-discriminatory power in predicting sepsis (area under the curve= 0.74, 95% CI, 0.71-0.77, p<0.001) and severe sepsis (AUC=0.70, 95% CI, 0.67-0.74, p<0.001). Conclusions: CAR was an independent predictor for the presence and severity of neonatal sepsis.